KEBIJAKAN PENDIDIKAN KARAKTER MELALUI PROFIL PELAJAR PANCASILA DALAM KONTEKS PERUBAHAN SOSIAL: LITERATURE REVIEW - Mahfud, Moh (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2023)
This research aims to conduct a literature review on the profile of Pancasila learners and character education and their relationship with social change. The research method chosen for this study is Systematic Literature Review (SLR). Data collection was carried out by documenting and reviewing articles that examined